Designing, Conducting, and Documenting Human Nutrition Plant-Derived Intervention Trials - Weaver, Connie M.; Hodges, J. Kalina (Frontiers in Nutrition, 2021)
Best practices for designing, conducting, documenting, and reporting human nutrition randomized controlled trials were developed and published in Advances in Nutrition. Through an example of the randomized clinical trial on blueberries and bone health funded by the National Institutes of Health, this paper will illustrate the elements of those best practices that apply specifically to plant-based intervention clinical trials. Unique study design considerations for human feeding interventions with bioactive plant compounds include the difficulty of blinding the intervention, the background nutritional status of participants, carry-over effects of the intervention, benefits of a run-in period, lack of safety/tolerability data, and nutrition-specific regulatory policies. Human nutrition randomized controlled trials are the gold standard for establishing causal relations between an intervention and health outcome measure. Rigorous studies and documentation define the quality of the evidence-base to inform public health guidelines and to establish personalized dietary recommendations for the health-promoting plant components.